Langmuir turbulence and filament frontogenesis in the oceanic surface boundary layer. (1st October 2019) - Sullivan, Peter P.; McWilliams, James C.
Abstract : Submesoscale currents, small-scale turbulence and surface gravity waves co-exist in the upper ocean and interact in complex ways. To expose the couplings, the frontogenetic life cycle of an idealized cold dense submesoscale filament interacting with upper ocean Langmuir turbulence is investigated in large-eddy simulations (LESs) based on the incompressible wave-averaged equations. The simulations utilize large domains and fine meshes with 6.4× 10^9 grid points. Case studies are made with surface winds or surface cooling with waves oriented in across-filament (perpendicular) or down-filament (parallel) directions relative to the two-dimensional filament axis. The currents u, v and w are aligned with the across-filament, down-filament and vertical directions, respectively. Frontogenesis is induced by across-filament Lagrangian secondary circulations in the boundary layer, and it is shown to be strongly impacted by surface waves, in particular the propagation direction relative to the filament axis. In a horizontally heterogeneous boundary layer, surface waves induce both mean and fluctuating Stokes-drift vortex forces that modify a linear, hydrostatic turbulent thermal wind (TTW) approximation for momentum. Down-filament winds and waves are found to be especially impactful, they significantly reduce the peak level of frontogenesis by fragmenting the filament into primary and secondary down-welling sites in a broad frontal zone over a width 500 m . At peak frontogenesis, opposing down-filament jets v overlie each other resulting in a vigorous vertical shear layer [STIX]x2202_zv with large vertical momentum flux v^′ w^′ . Filament arrest is induced by a lateral shear instability that generates horizontal momentum flux u^′ v^′ at low wavenumbers. The turbulent vertical velocity patterns, indicative of coherent Langmuir cells, change markedly across the horizontal domain with both across-filament and down-filament winds under the action of submesoscale currents.